Assessment of head trauma in children: Current guidelines and challenges (Research, Society and Development, 2024)
The objective of this research is to analyze and synthesize current guidelines for the assessment of head trauma in children, identifying challenges faced in implementing these guidelines in clinical practice. To search for eligible responses, a systematic literature review was carried out, the aim of which was to gather, analyze and synthesize all available evidence on the research topic. Searches in scientific literature were carried out in the following databases: Latin American and Caribbean Literature in Health Sciences - LILACS and National Library of Medicine - PUBMED. Analysis and synthesis of current guidelines for the evaluation of head trauma in children reveal a series of fundamental recommendations to ensure an effective and safe approach to the management of these complex cases. However, its implementation in clinical practice faces significant challenges that can impact the quality of care offered to children suffering from head trauma. One of the main challenges is the variability in interpretation and application of guidelines by healthcare professionals, due to the complexity and multifaceted nature of pediatric head trauma. Additionally, a lack of adequate resources, such as neuroimaging equipment and trained personnel, may limit the ability of healthcare facilities to follow all guideline recommendations.